2019
DOI: 10.3390/cancers11111647
|View full text |Cite
|
Sign up to set email alerts
|

Tumor and Cerebrospinal Fluid microRNAs in Primary Central Nervous System Lymphomas

Abstract: Primary central nervous system lymphoma (PCNSL) is a rare, highly aggressive, extranodal form of non-Hodgkin lymphoma, predominantly diagnosed as primary diffuse large B-cell lymphoma of the central nervous system (CNS DLBCL). Fast and precise diagnosis of PCNSL is critical yet challenging. microRNAs, important regulators in physiology and pathology are potential biomarkers. In 131 patients with CNS DLBCL and with non-malignant brain lesions (n-ML), miR-21, miR-19b and miR-92a, miR-155, miR-196b, miR-let-7b, m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
23
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 57 publications
5
23
0
Order By: Relevance
“…The utility of CSF miR-21, miR-19b, and miR-92a as PCNSL markers has been suggested [ 12 ]. We have recently confirmed [ 13 ] that the miR-21, miR-19b, and miR-92a levels were significantly higher in CSFs of patients with CNS DLBCL than of patients with non-malignant brain tumors; however, the diagnostic accuracy of those miRs was found to be lower than previously suggested. We also demonstrated that CNS DLBCL CSFs and the relevant brain biopsy samples are characterized by specific, different miR profiles [ 13 ].…”
Section: Introductionsupporting
confidence: 75%
See 3 more Smart Citations
“…The utility of CSF miR-21, miR-19b, and miR-92a as PCNSL markers has been suggested [ 12 ]. We have recently confirmed [ 13 ] that the miR-21, miR-19b, and miR-92a levels were significantly higher in CSFs of patients with CNS DLBCL than of patients with non-malignant brain tumors; however, the diagnostic accuracy of those miRs was found to be lower than previously suggested. We also demonstrated that CNS DLBCL CSFs and the relevant brain biopsy samples are characterized by specific, different miR profiles [ 13 ].…”
Section: Introductionsupporting
confidence: 75%
“…For HP examination, hematoxylin and eosin staining was performed. For IHC, tissue sections were incubated with the diluted antibodies for 1 h in an autostainer (Dako, Carpinteria, CA, USA) following the antigen-retrieval technique, if necessary, using the EnVision™ Detection Systems FLEX kit (Dako Corp., Carpinteria, CA, USA, code K 8000) and monoclonal antibodies (MoAbs) specific for CD20, CD10, BCL6, MUM1, BCL2, CD5, and Ki-67, as previously described [ 13 ]. A reaction for CD20, BCL6, MUM1, and CD5 was considered positive if at least 20% of the CNS DLBCL cells showed staining, while for CD10 if any cell showed staining.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Notably, these findings could be reproduced (sensitivity 97.4%) in an enlarged cohort ( n = 39) of PCNSL patients [ 50 ]. Furthermore, these data were confirmed by Zajdel et al with a lower diagnostic accuracy, which can be explained by the selection of a different reference group [ 27 ].…”
Section: Micrornassupporting
confidence: 58%